Rufinamide: crystal structure elucidation and solid state characterization - Salunke, Nita; Thipparaboina, Rajesh; Chavan, Rahul B.; Lodagekar, Anurag; Mittapalli, Sudhir; Nangia, Ashwini; Shastri, Nalini R. (Journal of Pharmaceutical and Biomedical Analysis, 2018)
Rufinamide (R) is a triazole derivative approved for the management of partial seizures and seizures associated with Lennox-Gastaut Syndrome, in November 2007. Crystal structure, solid state characterization, drug-excipient compatibility and solubility play a pivotal role in formulation development. This work deals with the crystal structure elucidation of R by single crystal X-ray diffraction and solid state characterization by thermal, spectroscopic and crystallographic techniques. Drug- excipient compatibility was assessed by differential scanning calorimetry (DSC). New RP-HPLC method for quantification of R was developed with improved retention time. Solubility and dissolution of drug in different media was determined. Additionally, the flow behavior of the drug was evaluated by measuring Carr's index and Hausner's ratio, while the compressibility behavior was studied using Well's protocol. R crystallized from dimethylformamide (R-DMF) was utilized for single crystal analysis. The drug crystallized in triclinic crystal system with P-1 space group. Asymmetric unit cell consists of two molecules of R held by intermolecular hydrogen bond (connected by N-H center dot center dot center dot O, which forms the catemeric chain). Analytical outcomes from DSC, thermogravimetric analysis (TGA) and powder X-ray diffraction (PXRD) revealed that the drug was present in pure crystalline form and was devoid of any polymorphic or pseudopolymorphic impurities. Influence of pH on the solubility and dissolution of R-DMF was found to be insignificant. The drug exhibited poor aqueous solubility, which was improved nearly 4.6 fold with the addition of 2% sodium lauryl sulphate (SLS). The drug exhibits poor flow and elastic compression nature. Excipients such as poly ethylene glycol (PEG) 8000, SLS, lactose monohydrate, starch and Hydroxypropyl methylcellulose (HPMC) E15 were incompatible with R-DMF as identified by thermal analysis. It is envisaged that these information regarding solid state properties of R-DMF would aid in identifying a logical path for formulation development. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Compressibility; Dissolution media; DSC; HPLC method; solubility

Co amorphous valsartan nifedipine system: Preparation, characterization, in vitro and in vivo evaluation - Lodagekar, Anurag; Chavan, Rahul B.; Mannava, M. K. Chaitanya; Yadav, Balvant; Chella, Naveen; Nangia, Ashwini K.; Shastri, Nalini R. (European Journal of Pharmaceutical Sciences, 2019)
Co amorphous systems are supersaturated drug delivery systems which offer a basic platform for delivery of multicomponent adducts (combination of more than one active pharmaceutical ingredient (API)) and/or as a fixed dose combination therapy, in addition to their potential to improve the apparent solubility, dissolution rate and ultimately bioavailability of poorly water soluble APIs. In the present work, a new drug-drug co amorphous system namely valsartan-nifedipine was prepared by quench cooling technique. Prepared co amorphous system was characterized for its solid state behavior with the help of Fourier Transform Infrared spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and Powder X Ray Diffractometry (PXRD). The optimized co amorphous system was stable for 1 month when exposed to accelerated stability condition (40 +/- 2 degrees C and 75 +/- 5% RH). The improved stability of amorphous nifedipine in co amorphous system was attributed to improved miscibility and intra and intermolecular non-covalent interactions mainly due to presence of hydrogen bonding between valsartan and nifedipine which was studied by FTIR analysis. Co amorphous systems were evaluated by mainly in vitro dissolution and in vivo benefit. In vitro dissolution study showed nearly 5.66 folds and 1.61 folds improvement which was translated to 3.63 and 2.19 times enhancement in vivo C-max for nifedipine and valsartan respectively.

Quantification of niclosamide polymorphic forms - a comparative study by Raman, NIR and MIR using chemometric techniques - Bhavana, Valmala; Chavan, Rahul B.; Mannava, M. K. Chaitanya; Nangia, Ashwini; Shastri, Nalini R. (Talanta, 2019)
Niclosamide, an anthelmintic drug recently repurposed for its activity against cancer, crystallizes into three solvated forms, two monohydrates (NHa, NHb) and one anhydrous (NAn) form. NAn is sensitive to pseudopolymorphic transformations that affect its dissolution and consequently, its bioavailability. NAn exhibits a polymorphic conversion to metastable monohydrate (NHa) form during high-energy milling in presence of poorly soluble solvents like water. It is hence very important to quantify polymorphic conversion from NAn to NHa, as water is a commonly used solvent during various processing like ball milling and wet granulation. This main objective of the study was to examine the feasibility of Raman, NIR and MIR spectroscopic techniques for identification and quantification of polymorphic forms of niclosamide in binary mixtures and multicomponent mixtures. Calibration models were developed and validated by vibrational spectroscopic techniques in binary mixtures of NAn and NHa and in multicomponent mixtures by chemometric techniques. These techniques were further used to identify and quantify NHa during ball milling, granulation and in presence of other polymorphic forms of niclosamide. Identification and quantification of pseudopolymorphs in binary and multicomponent mixtures with an acceptable recovery of 100.13-102.99% for Raman and 100.07-101.28% for NIR with low % RSD of 2.38-3.12 for both techniques were obtained. The % NHa determined during ball milling and granulation was similar by NIR and Raman. Raman spectroscopy however showed a greater advantage over other techniques in determining the NHa in presence of NHb due to significant difference in the spectral region of hydrates, when compared to NIR and MIR.
Keywords: Ball milling; Granulation; MSC; PLS; Polymorphic conversion; spectroscopy

The effects of cis and trans butenedioic acid on the physicochemical behavior of lumefantrine - Tomar, Devendrasingh; Lodagekar, Anurag; Gunnam, Anilkumar; Allu, Suryanarayana; Chavan, Rahul B.; Tharkar, Minakshi; Ajithkumar, T. G.; Nangia, Ashwini K.; Shastri, Nalini R. (Crystengcomm, 2022)
The present work investigates the effects of cis and trans butenedioic acid isomers (maleic acid and fumaric acid) on the crystallinity and pharmaceutical behavior of lumefantrine. Differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), attenuated total reflectance infrared spectroscopy (ATR-IR), solid-state nuclear magnetic resonance spectroscopy (ss-NMR), and single-crystal X-ray diffraction (SC-XRD) studies were employed. Lumefantrine-fumaric acid crystallized as a salt in the monoclinic space group P2(1)/c. In comparison, DSC and PXRD showed the formation of a co-amorphous solid with maleic acid. Complete proton transfer with a strong ionic interaction led to crystalline salt formation with the trans isomer, whereas weaker/fewer hydrogen bonds with the cis isomer of butenedioic acid led to a co-amorphous salt. The in vitro dissolution of both salts resulted in a similar 2.6-2.7-fold improvement in dissolution rate when compared to that of the crystalline lumefantrine. The crystalline and co-amorphous salts were stable under accelerated stability conditions (40 +/- 2 degrees C and 75 +/- 5% RH) for one month.